A study of semiconductor back-end manufacturing : special focus on scheduling techniques - Ong, Choon Keong (2014)
The purpose of this project was to study the impact of release input, lot dispatch and lot batching policies on the mean and variance of cycle time in the semiconductor back-end facility.